Hawai‘i Jungle Writing: Where There is the Most Life - Manley, Stewart (Taylor & Francis, 2019)
This autoethnography uses a series of loosely connected personal reflections, imaginative flights and academic commentary to explore life writing from the Hawaiian jungle. Jungle–the cacophonic chaos of ecologic diversity, memory, intersection, interdependence, fragility and, of course, impending end and rebirth–overflows with biology, yet is also threatened by it. The writing of the struggle of the jungle is nothing less than the writing of the struggle of life. To illuminate the intersection between jungle writing and life writing, the piece places writing of the jungle within the context of my own memories of Hawai‘i, the ecosystem surrounding my parents’ home, the threat to endemic jungle life, and the broader development and underlying themes of nature writing and ecocriticism. I also reflect on how writing of the jungle made me consider my own relationship with it and with life writing. The fragmented, somewhat disordered style of the piece reflects the jumbled and nonlinear nature of the jungle and of life. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.